Durkheim, the Durkheimians, and the arts - Riley, Alexander; Pickering, W. S. F.; Miller, Willie Watts (Berghahn Books, 2013)
Using a broad definition of the Durkheimian tradition, this book offers the first systematic attempt to explore the Durkheimians' engagement with art. It focuses on both Durkheim and his contemporaries as well as later thinkers influenced by his work. The first five chapters consider Durkheim's own exploration of art; the remaining six look at other Durkheimian thinkers, including Marcel Mauss, Henri Hubert, Maurice Halbwachs, Claude Lévi-Strauss, Michel Leiris, and Georges Bataille. The contributors-scholars from a range of theoretical orientations and disciplinary perspectives-are known f.